Addressing the Aesthetic Issues in Graphic Design as Visual Communication Media - Sonde Martadireja; Evi Hafizah (Institut Seni Indonesia Yogyakarta, 2026)
The study of aesthetics remains a crucial area in the discourse of graphic design worldwide. Various questions continually arise in tandem with cultural shifts and advancements in artificial intelligence technology, as is evident in the present era. This article attempts to provide alternative answers through a qualitative description utilizing the method of literary study. The diversity of aesthetic definitions, ranging from Plato’s ideologically influenced perspective to Baumgarten’s empirical approach, indicates that theological/metaphysical, positivistic, or even a combination of both values form the basis of aesthetic knowledge for a graphic designer. The influence of this aesthetic knowledge is manifested through the thought process in decision-making, from project acceptance considerations to determining the visual forms that will appear in the work. Through design psychology, the balance between aesthetics and communication content in a work can be interpreted as a meaningful representation of values by the designer as the embodiment of communicative ideas, and by the target audience as communicants. This also forms the basis for understanding and assessing the existence of collective aesthetics. The method for gauging collective aesthetics can be simulated by determining the maximum point values among the majority of the target audience, conceptualized as the safe boundary of collective aesthetics. The complexity of aesthetic issues within the scope of graphic design as a visual communication medium highlights the importance of multidimensional understanding to address each problem while guiding the work toward communicative and artistic goals.